2019
DOI: 10.1523/eneuro.0388-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillations in the Basolateral Amygdala: Biophysical Mechanisms and Computational Consequences

Abstract: The basolateral nucleus of the amygdala (BL) is thought to support numerous emotional behaviors through specific microcircuits. These are often thought to be comprised of feedforward networks of principal cells (PNs) and interneurons. Neither well-understood nor often considered are recurrent and feedback connections, which likely engender oscillatory dynamics within BL. Indeed, oscillations in the gamma frequency range (40 − 100 Hz) are known to occur in the BL, and yet their origin and effect on local circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 118 publications
(191 reference statements)
0
21
0
Order By: Relevance
“…BLA LFPs were characterized by evoked responses of the same width (approximately 9 ms) in the 8, 20, 50, and 50/8 Hz conditions (Figure 3B–F). The initial evoked responses were followed by smaller responses in the fast gamma range (60–120 Hz), which is a prominent frequency band in the amygdala (Amir et al, 2018; Feng et al, 2019). In contrast, CA1 LFPs during stimulation with blue light displayed a more continuous waveform that had a sawtooth shape for 8 and 20 Hz conditions and a sinusoidal shape for 50 Hz stimulation (Figure 3B–D).…”
Section: Resultsmentioning
confidence: 99%
“…BLA LFPs were characterized by evoked responses of the same width (approximately 9 ms) in the 8, 20, 50, and 50/8 Hz conditions (Figure 3B–F). The initial evoked responses were followed by smaller responses in the fast gamma range (60–120 Hz), which is a prominent frequency band in the amygdala (Amir et al, 2018; Feng et al, 2019). In contrast, CA1 LFPs during stimulation with blue light displayed a more continuous waveform that had a sawtooth shape for 8 and 20 Hz conditions and a sinusoidal shape for 50 Hz stimulation (Figure 3B–D).…”
Section: Resultsmentioning
confidence: 99%
“…6 , second line) and, at critical capacity, the neuron operates in a balanced regime in which inhibitory and excitatory currents are anti-correlated and largely cancel each other out ( Rubin et al, 2017 ). Experimentally, it has been shown that inhibitory postsynaptic currents are larger in magnitude than excitatory ( Atallah and Scanziani, 2009 ; Salkoff et al, 2015 ; Feng et al, 2019 ). Although Equation 14 derived in the N → ∞ limit yield a small positive or zero average postsynaptic input (high-weight regime), associative networks of finite-size loaded with memories to capacity show a trend consistent with the experimental measurements ( Zhang et al, 2019b ).…”
Section: Methodsmentioning
confidence: 99%
“…(6)] and, at critical capacity, the neuron operates in a balanced regime in which inhibitory and excitatory currents are anti-correlated and largely cancel each other out (Rubin et al, 2017). Experimentally, it has been shown that inhibitory postsynaptic currents are larger in magnitude than excitatory (Atallah and Scanziani, 2009;Salkoff et al, 2015;Feng et al, 2019). Though Eqs.…”
Section: The Solution In the Case Of Two Homogeneous Classes Of Inputsmentioning
confidence: 99%
“…The BLA also contains reciprocally connected PNs and FSIs, in similar proportions as in cortex (McDonald and Mascagni, 2001;Woodruff and Sah, 2007), and it too exhibits gamma (Bauer et al, 2007;Amir et al, 2018;Stujenske et al, 2014). Indeed, PNs and FSIs of the BLA preferentially spike during gamma oscillations in a manner similar to their cortical counterparts (Amir et al, 2018), and a detailed biophysical model of the BL nucleus generated gamma autonomously, reproducing the properties of gamma recorded in vivo (Feng et al, 2019).…”
Section: Complexity In the Temporal Domainmentioning
confidence: 58%